Stochastic structures in the low-frequency plasma turbulence: measurement of characteristics and determination of general features - Skvortsova, N.N.; Sarksyan, K.A.; Kharchev, N.K. (Вопросы атомной науки и техники, 2000)
Results are presented from the experimental and statistical studies of low-frequency turbulence in a magnetized plasma. It is shown that, for all types of driving instability (drift, ion-acoustic, MHD instability), this turbulence is accompanied by the formation of stochastic structures demonstrating a statistically consistent behavior and similar correlation, spectral, probability characteristics. The stochastic structures that are existing in the state of dynamic equilibrium and non-random interaction determine all common features of very different turbulent processes: ionacoustic nonlinear solitons, drift vortices, and MHD spatial structures. It follows that the structural turbulence is a non-Gaussian probability process with the long memory, i.e., a self-similar probability process.